Three-dimensional computed display of otosurgical operation sites by spiral CT - Schubert, Jan Ole; Sartor, Klaus; Forsting, Michael; Reisser, Christoph (Neuroradiology, 1996)
We studied the usefulness of spiral CT for preoperative information on the individual anatomy of the temporal bone in a computed three-dimensional (3D) display. In 87 patients with various otological diseases, 3D reconstructions were performed based on spiral high-resolution CT (HR-CT) by volume-rendering on an independent workstation. The positions of the ossicles, facial nerve, labyrinth and vestibular aqueduct relative to reference points were comprehensively demonstrated by thresholding or interactive segmentation. Spiral CT enables 3D display of otosurgical operation sites in a shorter scan time than conventional CT. 3D reconstructions improve the surgeon's understanding of individual anatomy and thus help in surgical planning. This is particularly important for surgery of temporal bone tumours, middle ear deformities, cochlear implants and saccotomy.